Junior Organization - San Jose State Normal School:::::::::
"War Work" is mentioned in many of the yearbooks published during World War I, including this description of the activities of one Junior class creating comfort bags for soldiers and raising money for a variety of relief efforts. (San Jose State La Torre, 1918 La Torre)